(untitled) (Bioagro, 2025)
Common bean is seriously affected by weeds interference, which can vary according to the weed’s emergence time and the crop’s planting season. This study aimed to evaluate the effects of relative times of Raphanus raphanistrum emergence on white beans in winter and summer season. An experiment was carried out for each season in 1.2 m x 1.2 m beds using a randomized block design, with Raphanus raphanistrum emergence times of 0, 10, 20, 30, 40, and 50 days after bean emergence (DABE) and a control without the weed, in four replications. Height, number of leaflets, chlorophyll content, leaf area and dry matter of stems, leaflets, and fruit were determined in the crop. Also, weight of grains and pods per plant, weight of 100 grains and yield at harvest. Furthermore, dry matter of Raphanus raphanistrum’s stems, leaflets, and fruit was determined. The data was subjected to analysis of variance using the F test, and means were compared using Tukey test at 5 % probability level. The lowest values for bean grain weight (152.72 g plant-1) and pod weight (223.67 g plant-1) in winter season were recorded when Raphanus raphanistrum emerged at 10 DABE. The summer season showed the lowest bean grain and pod weight values (81.45 and 121.5 g plant-1, respectively) when Raphanus raphanistrum emerged simultaneously with the crop. Raphanus raphanistrum emergence time altered its interference with beans. Moreover, planting season influenced crop and weed development, thus varying the effects of weed’s relative time of emergence on the crop.